Deficiency of Cathepsin K prevents inflammation and bone erosion in rheumatoid arthritis and periodontitis and reveals its shared osteoimmune role - Hao, Liang (FEBS Lett, 2015)
Using RA and periodontitis mouse models, we demonstrated that RA and periodontitis share many pathological features, such as deregulated cytokine production, increased immune-cell infiltration, increased expression of Toll-like receptors (TLRs), and enhanced osteoclast activity and bone erosion. We revealed that genetic deletion of Cathepsin K (Ctsk) caused a radical reduction in inflammation and bone erosion within RA joint capsules and periodontal lesions, a drastic decrease in immune-cell infiltration, and a significant reduction in osteoclasts, macrophages, dendritic and T-cells. Deficiency of Ctsk greatly decreased the expression of TLR-4, 5, and 9 and their downstream cytokines in periodontal gingival epithelial lesions and synovial RA lesions. Hence, Ctsk may be targeted to treat RA and periodontitis simultaneously due to its shared osteoimmune role.